Respuesta :

Answer:

[tex] \boxed{\sf Perimeter \: of \: rectangular \: garden = 10x + 2} [/tex]

[tex] \boxed{\sf Area \: of \: rectangular \: garden = 6x^2 + x - 2} [/tex]

Given:

Length of rectangular garden = 2x - 1

Width of rectangular garden = 3x + 2

Step-by-step explanation:

[tex] \sf Perimeter \: of \: rectangular \: garden = 2(Length + Width)[/tex]

[tex] \sf = 2((2x - 1) + (3x + 2))[/tex]

Grouping like terms:

[tex] \sf = 2((2x + 3x) + (2 - 1))[/tex]

2x + 3x = 5x:

[tex] \sf = 2(5x + (2 - 1))[/tex]

2 - 1 = 1:

[tex] \sf = 2(5x + 1)[/tex]

[tex] \sf = (2 \times 5x) + (2 \times 1)[/tex]

2 × 5x = 10x:

[tex] \sf = 10x + (2 \times 1)[/tex]

2 × 1 = 2:

[tex] \sf = 10x + 2[/tex]

[tex] \therefore[/tex]

Perimeter of rectangular garden = 10x + 2

[tex] \sf Area \: of \: rectangular \: garden = Length \times Width[/tex]

[tex] \sf = (2x - 1)(3x + 2)[/tex]

[tex] \sf = 2x(3x + 2) - 1(3x + 2)[/tex]

[tex] \sf = (2x \times 3x) + (2x \times 2) - (1 + 3x) - (1 \times 2)[/tex]

2x × 3x = 6x²:

[tex] \sf = 6 {x}^{2} + (2x \times 2) - (1 + 3x) - (1 \times 2)[/tex]

2x × 2 = 4x:

[tex] \sf = 6 {x}^{2} + 4x - (1 + 3x) - (1 \times 2)[/tex]

1 × 3x = 3x:

[tex] \sf = 6 {x}^{2} + 4x - 3x - (1 \times 2)[/tex]

1 × 2 = 2:

[tex] \sf = 6 {x}^{2} + (4x - 3x) - 2[/tex]

4x - 3x = x:

[tex] \sf = 6 {x}^{2} + x - 2[/tex]

[tex] \therefore[/tex]

Area of rectangular garden = 6x² + x - 2

Answer:

Perimeter = 10x+2 m

Area = 6x²+x-2 m²

Step-by-step explanation:

Length of garden (l) = 2x-1

width or breadth of garden ( b) = 3x+2

Now,

Perimeter of the garden (p) = 2( l + b)

= 2 ( 2x-1 + 3x+2 )

= 2 ( 5x + 1 )

= 10x+2 m. ( Answer )

Again,

Area of garden (a) = l * b

= ( 2x-1 ) ( 3x+2 )

= 2x ( 3x+2 ) -1 ( 3x+2 )

= 6x² + 4x - 3x - 2

= 6x²+x-2 m². ( Answer )